2018
DOI: 10.3389/fimmu.2018.02273
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 Molecular Dynamics in Treg in Juvenile Idiopathic Arthritis

Abstract: Since the identification of the regulatory T-cell (Treg)-associated transcription factor Foxp3, there have been intensive research efforts to understand its biology and roles in maintaining immune homeostasis. It is well established that thymic selection of a repertoire of self-reactive Foxp3+ T-cells provides an essential mechanism to minimize reactions to self-antigens in the periphery, and thus aid in the prevention of autoimmunity. It is clear from both genetic and immunological analyses of juvenile idiopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
1
16
0
2
Order By: Relevance
“…scRNA‐seq data were also generated on Tregs sorted from synovial fluid of patients with JIA, which complements prior detailed analyses of JIA synovial Treg phenotypes ( 43 ). Cytometric, imaging, and functional studies have demonstrated substantial heterogeneity of Tregs in JIA synovial fluid, including a subset of functional CD25 hi CD127 − Tregs that have downregulated FoxP3 expression ( 43 ) and subpopulations that differ in CD161 expression ( 44 ). Whether these Treg subpopulations can be discriminated transcriptomically remains to be demonstrated.…”
Section: High‐dimensional Views Of T‐cell Infiltrates In Rheumatic Diseasesmentioning
confidence: 99%
“…scRNA‐seq data were also generated on Tregs sorted from synovial fluid of patients with JIA, which complements prior detailed analyses of JIA synovial Treg phenotypes ( 43 ). Cytometric, imaging, and functional studies have demonstrated substantial heterogeneity of Tregs in JIA synovial fluid, including a subset of functional CD25 hi CD127 − Tregs that have downregulated FoxP3 expression ( 43 ) and subpopulations that differ in CD161 expression ( 44 ). Whether these Treg subpopulations can be discriminated transcriptomically remains to be demonstrated.…”
Section: High‐dimensional Views Of T‐cell Infiltrates In Rheumatic Diseasesmentioning
confidence: 99%
“…The phenotype of CD4 + FOXP3 + Tregs in JIA has been considerably characterized in the past (6) with the molecular roles of FOXP3 in JIA reviewed by Copland and Bending in this special collection (7). It is now clear that the Treg TCR (T cell receptor) repertoire is highly restricted in JIA, both at the site of inflammation (811) and in circulation (10, 12).…”
Section: Altered Tregs In Jia and Jdmmentioning
confidence: 99%
“…Tregs, which were first reported by Sakaguchi et al 15 as a subset of T cells with a CD4 + CD25 - high phenotype, play an important role in regulating immune tolerance of the tumor microenvironment. Recent studies have found that FOXP3 + is also an important phenotype of Tregs 1617. Zhao et al 17 found that the number of Tregs obviously increases in the bone metastatic microenvironment of prostate cancer.…”
Section: Tumor-infiltrating Lymphocytes and Prostate Cancermentioning
confidence: 99%